Indonesian Twitter Users Language Attitude Towards English-Indonesian Code-mixing - Rizky, Muhammad; Purwanti, Indah Tri; Aruan, Rumiri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Social media users need language as a tool to communicate, both in verbal and written form. Over time, the language used in social media also shows some significant growth. Talking about language in social media, there is an interesting phenomenon recently on social media that can be reached within the internet, namely the code-mixing of Indonesian and English (which in Indonesian are also popularly known as Jaksel language, Keminggris, Kemlondo, Indoglish, Englonesian, or Bahasa Gado-gado). This study is aimed to find out the attitudes of 500 Indonesian Twitter users towards English-Indonesian code-mixing with a questionnaire. This study uses a descriptive-quantitative approach. For the result of each aspect, it shows a quite positive indication: Cognitive aspect 2.92, Affective aspect 2.75, and Conative 2.79. If the three aspects being summed up, also indicated a quite positive attitude towards the code-mixing with point or score 2.82. The attitudes come from many reasons and factors, such as the need for understandability in communication, language prestige, prepossessing or attracting attention, confidence, and language aptitude.